Health Belief Model of Jambi City Community Against Covid-19 Vaccination with Structural Equation Modeling (SEM) Method - Sherli Yurinanda; Cut Multahadah; Susi Marisa (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
The community's HBM (Health Belief Model) analysis of the COVID-19 vaccination needs to be done. This perceived threat assessment is based on perceived vulnerability and seriousness. Judgments to behave in response to perceived threats are also influenced by cues to action. Variables that cannot be explained directly or variables that require explanation from other variables are called latent variables. Latent variables consist of exogenous and endogenous variables. This study aims to analyze the public health belief model of the city of Jambi towards COVID-19 vaccination with the structural equation modeling (SEM) method. The results showed that the health belief model for COVID-19 vaccination in Jambi City, vaccination actions were significantly influenced by perceptions of benefits and barriers. Perceived benefits and barriers were significantly affected by perceived severity and seriousness and then perceived severity and seriousness were significantly influenced by cues to action. However, demographics including age, occupation, income and beliefs in this study did not significantly influence a person to vaccinate. The proposed model can be accepted based on the goodness of fit indicator